The Role of Regulatory T Cells in Contact Hypersensitivity - Honda, Tetsuya; Miyachi, Yoshiki; Kabashima, Kenji (Recent Patents on Inflammation & Allergy Drug Discovery, 2010)
Regulatory T cells (Tregs) are one of the T cell subsets that have strong immune-suppressive activity. Contact hypersensitivity (CHS), clinically manifested as contact dermatitis, is one of the most frequently used mouse models to address cutaneous immune responses, and is composed of two phases: sensitization and elicitation. Recently, the role of Tregs in CHS has been investigated using newly generated genetically engineered mice. In this review, we will provide an overview of recent patents and the mechanism of Treg-mediated immunosuppression especially in terms of IL-10, CD39, CTLA-4, and RANKL, and discuss the role of Tregs in CHS during the sensitization and elicitation phases.
Keywords: Foxp3